Efficacy and risk profile of anti-diabetic therapies: Conventional vs traditional drugs—A mechanistic revisit to understand their mode of action. (November 2016) - Gupta, Prachi; Bala, Manju; Gupta, Sanjeev; Dua, Anita; Dabur, Rajesh; Injeti, Elisha; Mittal, Ashwani
Graphical abstract: Abstract: An increasing array of anti-diabetic drugs are available today, yet Type-2 diabetes mellitus (T2DM) – remains a life threatening disease, causing high mortality and morbidity in developing and developed countries. As of now, no effective therapy is available for the complete eradication/cure of diabetes and its associated complications. Therefore, it is time to re-think and revisit molecular pathways and targets of each existing drug in order to identify multiple targets from different signaling pathways that may be manipulated simultaneously to treat or manage T2DM effectively. Bearing this goal in mind, the article reviews the mechanisms of action of available anti-diabetic drugs with in-depth mechanistic analysis of each therapy. The conventional and herbal strategies are analysed and compared for their benefits and the associated possible side effects. This critical information is necessary not only for the development of better, novel and potent anti-diabetic therapy in future but also for best possible combinational therapies and strategies with the available drugs.